DEVELOPMENT OF A HYBRID TOURISM MODEL TO PROMOTE COMMUNITY-BASED EXPERIENTIAL TOURISM: A CASE STUDY OF PHROM KHIRI DISTRICT, NAKHON SI THAMMARAT PROVINCE - Sutthikhun, Pornfar; Nillakan, Lunjakon; Lertgrai, Punya (Journal of MCU Nakhondhat, 2026)
This research aimed to 1) Analyze the problems and potential of a hybrid tourism model, 2) Develop a hybrid tourism model, and 3) Evaluate the effectiveness of the developed model. The study employed a Research and Development (R&D) approach. The key informants consisted of stakeholders involved in tourism development, including 10 members of the Phrom Lok Tourism Club, 8 members of the Ban Nai Mong Tourism Group, and 100 tourists. The research instruments included document analysis, in-depth interviews, focus group discussions, field surveys, a model suitability evaluation form, and a tourist satisfaction questionnaire. Data were analyzed using content analysis, mean, and standard deviation. The findings revealed that Phrom Khiri District, Nakhon Si Thammarat Province, possesses abundant tourism resources, including natural attractions, cultural heritage, local ways of life, indigenous wisdom, and agricultural resources, all of which have strong potential for developing experiential tourism activities. However, several challenges were identified, including insufficient integration among tourism activities, limited tourism marketing and promotion, and ineffective tourism management. The study developed the PHROM KHIRI Hybrid Tourism Experience Model, comprising ten key components: 1) Community participation, 2) Hybrid tourism activities, 3) Integration of tourism resources, 4) Tourism management, 5) Marketing and digital media, 6) Local wisdom learning, 7) tourist services and experiences, 8) Innovation for sustainable tourism, 9) Community networks and collaboration, and 10) Continuous evaluation and development. The model was evaluated by experts and was rated at the highest level of appropriateness. Following implementation in the study area, the overall satisfaction of tourists with the model was at the highest level ( = 4.72), while community satisfaction was also at the highest level ( = 4.65). The developed model effectively promotes community-based experiential tourism, enhances tourism potential, generates local income, strengthens community participation, and supports sustainable community development.